Practical skills of psychology bachelors in working with automated HR platforms - P. Bleshmudt; O. Fil (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія")
The aim was to identify recommendations for future specialists in the field of psychology on the use of modern human resources (HR) platforms. The functionality of modern online platforms used in HR management is analysed. The study of the experience of leading companies, a survey of students and teachers, and a comparative analysis of HR platforms in three countries, namely Ukraine, the USA, and Germany, were described. The main results of the study demonstrated that the introduction of automated HR platforms into the educational process contributes to a significant improvement in the practical skills of bachelors of psychology. Students have acquired not only basic knowledge but also experience with modern HR systems such as SAP SuccessFactors, Workday and BambooHR, which has enabled them to better prepare for their future professional activities. The analysis of the results showed that the use of such platforms helped students to master key competencies in performance evaluation and transparent communication in the team. The introduction of HR platforms has had a positive impact on students' awareness of modern HR management tools, increased their adaptability to the latest technologies and readiness to work in remote and international environments. The integration of such platforms into the curriculum helped students to be prepared for the real challenges of the modern labour market, where HR technologies play a key role. Students who learn how to work with these platforms gain a competitive advantage, as many companies are looking for professionals who can effectively use digital technologies. Particular attention should be paid to improving data security, which is becoming critical when working with HR platforms, as employees’ personal data needs to be protected from unauthorized access. This study can be used by teachers of higher education institutions and HR managers to introduce modern HR platforms into the educational process and training of future psychology professionals